Índice biespectral, efeitos hemodinâmicos e respiratórios da infusão contínua de propofol associado ou não ao fentanil em bezerros - Deschk, Mauricio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate the bispectral index and hemodynamic, respiratory and blood gas effects of continuous infusion of propofol with or without fentanyl in calves. Eight animals were used, with six to 12 months old, male Holstein calves, with an average weight of 123 ± 18 kg. All animals participated in both groups, respecting always a minimum interval of one week between the anesthetic procedures, the calves were randomly distributed between groups. They were induced to anesthesia with propofol at a dose of 5 mgkg-1 IV control group (GP) or propofol 4 mg kg-1 associated with fentanyl 0.001mgkg-1 IV fentanyl group (GF) and positioned in right lateral decubitus, where remained spontaneously breathing room air. Subsequently, the Anesthesia was maintained by continuous infusion of propofol at the rate of 0.6 mg kg-1 min-1 IV, with or without the infusion of fentanyl 0.001mg kg-1 hour-1. In both groups, drugs were administered through an infusion pump over 60 minutes. The measurements of hemodynamic parameters (HR, SAP, DAP, MAP, CO, CVP, mPAP, mPAPO, CI, SI, SVRI and PVRI), respiratory (ETCO2, f, SpO2,VME and VTE), blood gas(PaO2, PaCO2, SaO2, DB, pHandHCO3-) and bispectral index (BIS, SQI and EMG) were evaluated before anesthesia induction(MB), 15, 30, 45 and 60 minutes after the beginning of continuous infusion of drugs (M15, M30, M45 and M60, respectively). Hemodynamic parameters remained stable during the evaluate on period, no significant differences were observed between the groups in the respiratory variables and BIS, however, all animals presented respiratory acidosis. With the infusion of propofol associated or not with fentanyl the maintenance of the hemodynamic parameters was satisfactory with respiratory acidosis indicating, therefore, the use of mechanical ventilation

O estudo teve por objetivo avaliar o índice biespectral e os efeitos hemodinâmicos, respiratórios e hemogasométricos da infusão contínua de propofol associado ou não ao fentanil em bezerros. Foram utilizados oito animais machos entre seis e doze meses de idade, holandeses, com massa corporal média de 123 ± 18 kg. Todos os animais participaram de ambos os grupos, respeitando-se sempre um intervalo mínimo de uma semana entre uma anestesia e outra, os bezerros foram aleatoriamente distribuídos entre os grupos. Os animais foram induzidos à anestesia com propofol na dose de 5 mg/kg; IV, grupo controle (GP) ou propofol 4 mg/kg associado ao fentanil 0,001 mg/kg; IV, grupo fentanil (GF) e posicionados em decúbito lateral direito, onde permaneceram respirando espontaneamente ar ambiente. Ato contínuo, a manutenção anestésica foi realizada pela infusão contínua de propofol na taxa de 0,6 mg/kg/minuto; IV, associado ou não à infusão de fentanil 0,001 mg/kg/hora.Em ambos os grupos os fármacos foram administrados por meio de bomba de infusão durante 60 minutos. A mensuração das variáveis hemodinâmicas (FC, PAS, PAD, PAM, DC, PVC, PAPm, PAPOm, IC, IS, IRVS e IRVP), respiratórias (ETCO2, f, SpO2, VTE e VME), hemogasométricas (PaO2, PaCO2, SaO2, DB, pH e HCO3-) e indice bispectral (BIS, IQS e EMG) foi feita antes da indução anestésica (MB), e 15, 30,45 e 60 minutos após o início da infusão contínua dos fármacos (M15, M30, M45 e M60, respectivamente). Os parâmetros hemodinâmicos mantiveram-se estáveis durante o período de avalição, não foram observadas diferenças significativas entre os grupos nas variáveis respiratórias ou no BIS, porém, todos os animais apresentaram depressão respiratória e acidose. Com a infusão de propofol associado ou não ao fentanil obteve-se manutenção satisfatória dos parâmetros hemodinâmicos com depressão respiratória, indicando, portanto, a necessidade do emprego de ventilação...
Bispectral index, hemodynamic and respiratory effects of continuous infusion propofol associated or not to fentanyl in calves
Keywords: Bovino; Propofol; Anestesia animal; Hemodinâmica; Índice bispectral; Ruminante; Bispectral index (BIS); Cattle